First Evidence for Internal Ribosomal Entry Sites in Diverse Fungal Virus Genomes - Chiba, Sotaro (mBio, 2018)
In contrast to well-established internal ribosomal entry site (IRES)-mediated translational initiation in animals and plants, no IRESs were established in fungal viral or cellular RNAs. To identify IRES elements in mycoviruses, we developed a luciferase-based dual-reporter detection system in Cryphonectria parasitica, a model filamentous fungus for virus-host interactions. A bicistronic construct entails a codon-optimized Renilla and firefly luciferase (ORluc and OFluc, respectively) gene, between which potential IRES sequences can be inserted. In this system, ORluc serves as an internal control, while OFluc represents IRES activity. Virus sequences in the 5′ untranslated regions (UTRs) of the genomes of diverse positive-sense single-stranded RNA and double-stranded RNA (dsRNA) viruses were analyzed. The results show relatively high IRES activities for Cryphonectria hypovirus 1 (CHV1) and CHV2 and faint but measurable activity for CHV3. The weak IRES signal of CHV3 may be explained by its monocistronic nature, differing from the bicistronic nature of CHV1 and CHV2. This would allow these three hypoviruses to have similar rates of translation of replication-associated protein per viral mRNA molecule. The importance of 24 5′-proximal codons of CHV1 as well as the 5′ UTR for IRES function was confirmed. Furthermore, victoriviruses and chrysoviruses tested IRES positive, whereas mycoreoviruses, partitiviruses, and quadriviruses showed similar Fluc activities as the negative controls. Overall, this study represents the first development of an IRES identification system in filamentous fungi based on the codon-optimized dual-luciferase assay and provides evidence for IRESs in filamentous fungi.